2000
DOI: 10.1212/wnl.55.6.763
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the cystatin C gene is a novel risk factor for late-onset Alzheimer’s disease

Abstract: The reduced or absent risk for AD conferred by APOE in older populations has been well reported in the literature, prompting the suggestion that additional genetic risk factors confer risk for later-onset AD. In the author's dataset the opposite effects of APOE and CST3 genotype on risk for AD with increasing age suggest that CST3 is one of the risk factors for later-onset AD. Although the functional significance of this coding polymorphism has not yet been reported, several hypotheses can be proposed as to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 36 publications
3
70
1
1
Order By: Relevance
“…4 Cystatin C is also believed to inhibit A␤ production and aggregation by the inhibition of cathepsins, a group of lysosomal proteases believed to promote A␤-amyloidogenesis. 26 Finally, there is genetic data that support a causal role for cystatin C in the development of AD, [8][9][10]27 although there are conflicting findings. 28 Interestingly, the Icelandic form of hereditary cerebral hemorrhage with amyloidosis is caused by a mutation in the cystatin C gene, and these patients are characterized by low levels of cystatin C in CSF as well as in the systemic circulation, increased deposition of A␤ in cerebral blood vessels, dementia and death before age 40 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Cystatin C is also believed to inhibit A␤ production and aggregation by the inhibition of cathepsins, a group of lysosomal proteases believed to promote A␤-amyloidogenesis. 26 Finally, there is genetic data that support a causal role for cystatin C in the development of AD, [8][9][10]27 although there are conflicting findings. 28 Interestingly, the Icelandic form of hereditary cerebral hemorrhage with amyloidosis is caused by a mutation in the cystatin C gene, and these patients are characterized by low levels of cystatin C in CSF as well as in the systemic circulation, increased deposition of A␤ in cerebral blood vessels, dementia and death before age 40 years.…”
Section: Resultsmentioning
confidence: 99%
“…Cystatin C is an endogenous cysteine inhibitor, produced by nearly all human cells and available in all body fluids. 1 During the past decade, experimental, 2-7 genetic, [8][9][10] and clinical data 6,11,12 have suggested that cystatin C activity in the brain may protect against the development of Alzheimer disease (AD) by inhibition of A␤ aggregation, one of the pathologic hallmarks of AD. 13 Recently, it was shown that in a transgenic mouse model, cystatin C binds to soluble A␤, preventing its deposition in the brain.…”
Section: Conclusion: Low Levels Of Serum Cystatin C Precede Clinicalmentioning
confidence: 99%
“…The initial report identified the GG genotype with AD risk for survivors to ages 80 years and older (p ϭ 0.04). 6 Subsequently, a two-loci haplotype labeled B for promoter region and exon 1 G/A polymorphisms (n ϭ 907) 1 demonstrated a fourfold elevated risk, higher at age 75 years and older. A Japanese sample did not indicate a statistically significant association for CST 3 AA/AG or for APOE4 (low frequency among Japanese).…”
Section: Methodsmentioning
confidence: 99%
“…3 A polymorphism associated with AD is located in exon 1: A G/A transition results in Ala/Thr as the penultimate amino acid of the signal peptide, thought to reduce secretion and constitutive extracellular levels. 1,[4][5][6] The GG genotype doubles the risk in patients at ages 80 and older. 6 Subsequent studies did not replicate this finding or the associated risk with the A allele and at younger ages.…”
mentioning
confidence: 99%
See 1 more Smart Citation